Pengaruh Tingkat Pengangguran dan Zakat terhadap Pertumbuhan Ekonomi pada Negara ASEAN Tahun 2014–2023 - Fitri Rahmadhani; Agustina Mutia; Sri Rahma (Lembaga Yasin AlSys, 2026)
Economic growth, as a long-term process characterized by rising per capita income and structural transformation, requires an optimal resource management system, yet remains challenged by unstable growth, unemployment, inflation, and global recessionary pressures in 2023. This study aims to analyze the effects of unemployment and zakat on economic growth in three ASEAN countries (Indonesia, Malaysia, and Singapore), which were purposively selected based on their relatively more established zakat management regulations. A quantitative approach was employed using panel data regression analysis on secondary data for the 2014–2023 period. The results show that, individually, the unemployment rate has a negative but statistically insignificant effect on economic growth, whereas zakat has a negative and statistically significant effect on economic growth. Jointly, both variables significantly affect economic growth in the three ASEAN countries under study. These findings indicate that, within the context of this research, the level of unemployment has not yet been sufficiently large to exert a significant influence on growth, while zakat has a statistically meaningful impact. Therefore, optimal and efficient zakat management has the potential to serve as an important instrument for promoting economic development, reducing inequality, and improving societal welfare.